Severe Hypoalbuminemia Increases the Risk of Thrombocytopenia in Critically Ill Adult Patients Receiving Teicoplanin - Hasan, Md Jahidul; Rabbani, Raihan; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Teicoplanin is a drug of choice for treating infections by gram positive microorganisms. Teicoplanininduced thrombocytopenia is an adverse drug reaction found in critically ill patients receiving teicoplanin. The aim of this observational study was to analyze the increased risk of occurring teicoplanin-induced thrombocytopenia in patients with severe hypoalbuminemia than the patients having normal blood-albumin level. A 5-month long study was conducted in an adult-ICU department on 42 critically ill adult patients. In this study, 17 (40.48%, n=42) patients developed teicoplanin-induced thrombocytopenia and among them, 14 patients (60.87%, n=23) were suffering from severe hypoalbuminemia during the initiation of teicoplanin therapy. All the events were normalized within 48 hours after discontinuing the teicoplanin. In this study, we found that teicoplanin-induced thrombocytopenia is one of the most common adverse drug reaction developed in critically ill adult patients and concurrent severe hypoalbuminemia may enormously increase the risk of this adverse drug reaction. Dhaka Univ. J. Pharm. Sci. 18(2): 153-157, 2019 (December)